Order Patterns Networks (ORPAN)—a method to estimate time-evolving functional connectivity from multivariate time series - Schinkel, Stefan; Zamora-López, Gorka; Dimigen, Olaf; Sommer, Werner; Kurths, Jürgen (Frontiers in Computational Neuroscience, 2012)
Complex networks provide an excellent framework for studying the function of the human brain activity. Yet estimating functional networks from mea- sured signals is not trivial, especially if the data is non-stationary and noisy as it is often the case with physiological recordings. In this article we propose a method that uses the local rank structure of the data to deﬁne functional links in terms of identical rank structures. The method yields temporal se- quences of networks which permits to trace the evolution of the functional connectivity during the time course of the observation. We demonstrate the potentials of this approach with model data as well as with experimental data from an electrophysiological study on language processing.